Vibrations, waves, and acoustics - Chattopadhyay, D (Books and Allied, 2010)
Vibrations, waves, and acoustics / Chattopadhyay, D. -- Kolkata: Books and Allied, 2010 534 C495e8 8th ed No. of Copies : 1